2015
DOI: 10.1039/c5tc02247a
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-threshold up-converted lasing in oligofluorenes with tailored strong nonlinear absorption

Abstract: ae Nonlinear optical response in organic semiconductors has been an attractive property for many practical applications. For frequency up-converted lasers, to date, conjugated polymers, fluorescent dyes and small organic molecules have been proposed but their performances have been severely limited due to the difficulty in simultaneously achieving strong nonlinear optical response and high performance optical gain. In this work, we show that structurally designed truxene-based star-shaped oligofluorenes exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 54 publications
(111 reference statements)
1
26
0
Order By: Relevance
“…2.0 mJ) in DMSO, [3c] PhN-OF(5)-NPh (ca. 267 mJ) in solid state, [16] and even better than that of colloidal nanoplatelets (ca. 267 mJ) in solid state, [16] and even better than that of colloidal nanoplatelets (ca.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…2.0 mJ) in DMSO, [3c] PhN-OF(5)-NPh (ca. 267 mJ) in solid state, [16] and even better than that of colloidal nanoplatelets (ca. 267 mJ) in solid state, [16] and even better than that of colloidal nanoplatelets (ca.…”
Section: Methodsmentioning
confidence: 93%
“…1.5 mJ) in toluene, [17] tailored truxene oligomer (T6) (ca. 267 mJ) in solid state, [16] and even better than that of colloidal nanoplatelets (ca. 1.2 mJ) in solution.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Two‐photon absorption (TPA) exhibits the process in which substance simultaneously absorbs two photons to an excited state under the excitation of a strong laser ,. Recently, organic materials with excellent two‐photon absorption properties have been widely investigated and applicated in different aspects, including optical limiting, up‐converted lasing, 3D optical data storage, micro‐fabrication, photodynamic therapy, and two‐photon laser scanning fluorescence imaging, etc . Actually, the molecular structures strongly affect the TPA properties.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Recently, organic materials with excellent two-photon absorption properties have been widely investigated and applicated in different aspects, including optical limiting, up-converted lasing, 3D optical data storage, micro-fabrication, photodynamic therapy, and two-photon laser scanning fluorescence imaging, etc. [31][32][33][34][35][36] Actually, the molecular structures strongly affect the TPA properties. Studies showed that the appropriate choices of donor, acceptors and π-bridges [37,38] inducing appropriate intraor inter-molecular dipola moments are important for the TPA properties.…”
Section: Introductionmentioning
confidence: 99%